Conservation of non-crop plants as a management strategy to improve functional biodiversity in chili pepper crops - Martinez Chiguachi, Juliana Andrea (2018)
Management practices used within cropping systems play an important role in the ecosystem, because they can cause impacts on biodiversity. Practices such as the conservation of non-crop plants and the reduction of pesticides can favor populations of arthropods that perform functions within the agroecosystem, offering a greater availability of alternative resources. In this study, we carried out field and laboratory experiments. In fields of chili pepper, we evaluated in chili pepper fields the effect of three different management practices: (i) conservation of non-crop plants and non-application of pesticides, (ii) without non-crop plants and non-application of pesticides and (iii) conventional management (application of pesticides) on populations of different functional groups and on the abundance and diversity of insects of the family Coccinellidae. In the same crop system, we evaluated the abundance of Coccinellidae in relation to the abundance of prey potential and alternative resources available in the crop of chili pepper with and without the presence of non-crop plants. Additionally, in the laboratory, we evaluated the predation of first instar larvae of the coccinellid species Eriopis connexa and Harmonia axyridis on broad mites as an alternative food. Also, we quantified survival of these species feeding on broad mites and on floral resources of Ageratum conyzoides, a non-crop plant commonly found in and around cropped areas. As results, we found that the management system with the conservation of non-crop plants and the non-application of pesticides positively affected the abundance of functional groups such as predators, parasitoids, pollinators and herbivores, as well as the abundance and diversity of coccinellid predators. Furthermore, different species of coccinellids were found with the highest relative abundance of Scymnus rubricaudus, Brachiacantha groendali, Hyperaspis festiva and Cycloneda sanguinea. Besides, we confirmed that the management of non-crop plants through their conservation favors the abundance of coccinellids in comparison to fields of chili pepper without non-crop plants. First instar larvae of E. connexa and H. axyridis fed on different stages of the broad mite. Both species increased survival when broad mites and floral sources of A. conizoides were supplied together, but only E. connexa survived more days when only broad mites were supplied. However, none of the species completed larval development. Therefore, management practices implemented in the chili pepper crop that aim to reduce the application of pesticides and to conserve the non-crop plants can contribute to an increase in biodiversity, improve the abundance and diversity of coccinellid predators, and provide alternative resources that favor survival of these predators.